Прогнозування графіків електричних навантажень об'єднаної енергосистеми на довгострокову перспективу - Kulyk М.M.; Dubovskoy S.V.; Kobrin P.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
In article the method of shaped displays intended for long-term prediction the electric loading diagrams of electric power pools in conditions of transitive economy is given. The method was worked out in Institute of General Energy of Ukrainian National Academy of Science. Basic feature of this method is that it does not work with temporary rows and does not use the revealed dependences. The method is constructed on so-called shaped display.